Melawat di Simeulue (Studi Kasus di Desa Lambaya Kec. Simeulue Tengah dengan Desa Sanggiran Kec. Simeulue Barat Kabupaten Simeulue) - Rita Safari; Abdul Manan; Sanusi Ismail (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study aims to find out the history of visiting Simeulue, the visiting procession the Lambaya Village with Sanggiran Village, the role of the community in preserving visiting traditions and the benefits of visiting the people of Lambaya Village with Sanggiran Village. This study uses a descriptive qualitative research method with data collection techniques in the form of interviews, observation, and documentation. The results of the study indicate that visiting procession is a visit activity carried out by a group of individuals, organizations or communities by way of deliberations with citizens, communicating, and preparing all the necessities and interests of visiting activities. This visit is led by the highest person in the village or someone who is trusted as the leader of the activity group. The role and benefits of the community to preserve the tradition of visiting is that the community continues to maintain, apply, maintain and develop traditions and cultural values so that visiting can strengthen harmony in daily life. In addition, by visiting them they can get new experiences, find out weaknesses, lack of organization, keep them away from enmity, get new families and most importantly get knowledge that they have not yet gotten.